Dampak Penutupan Tiktok Shop Dalam Penjualan Produk: (Studi Kasus Pedagang Tiktokshop Di Desa Ambokembang, Kedungwuni) - Faesal Faesal; Nada Muna Luqyana; Naili Sa'idah; Gunawan Aji (Universitas 45 Surabaya, 2024)
TikTok Shop is a social commerce feature that allows users and content creators to promote and sell their products through TikTok. The impact of e-commerce on the Indonesian economy has been enormous, causing the country to experience unprecedented growth in this sector. TikTok Shop, an investment project in the popular social media application TikTok, was initially a huge success, making it easier for businesses and customers to interact in unique ways. However, this growth changed significantly after the TikTok Shop in Indonesia closed. The aim of this research is to determine the impact that occurred as a result of the TikTok shop being closed. This research uses a descriptive qualitative research approach. The results of this research are that the closure of the TikTok Shop has a significant impact on product sales. This impact can be positive or negative. The positive impact is that it can increase competition in the e-commerce industry. However, the negative impact is that it can cause a decrease in sales for sellers, difficulty finding alternative e-commerce platforms, and the loss of COD payment methods.